Hyperglycemia Induced by COVID-19 with and without Present Diabetes: A Systematic Review - Gembong Satria Mahardhika (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2021)
Abstract—COVID-19 is a major emerging disease that affects any certain condition. However, a recent report suggests the occurrence of hyperglycemia without any present diabetes in COVID-19 patients. This study aimed to systematically review recent evidence on hyperglycemia in COVID-19 patients. Literature research was done using four search engines, consist of Google Scholar, PubMed, ScienceDirect, and ProQuest, and limited to English manuscript only and published from February 2020 to September 2020. SARS-CoV-2 could damage the pancreas by causing the destruction of the β-cell structure that leads to impairment of glucose metabolism and worsen pre-existing diabetes or determine the appearance of hyperglycemia in non-diabetes. Inflammation also plays a major important role in hyperglycemia related to COVID-19. Hyperglycemia increased the vulnerability of the lung, by promoting and facilitating the entry of the SARS-CoV-2 into the host cells, and decreasing lung function. Moreover, the mortality and morbidity rate conceivable increased due to hyperglycemia. The presence of high glucose levels is linked with the progression of COVID-19 severity. Thus, the glucose level should be concerned, either in a patient with present diabetes or without any presence of diabetes. Examination and monitoring of glucose levels might be a useful tool to prevent the seriousness of COVID-19 Keywords: diabetes mellitus, SARS-CoV-2, high glucose level, pulmonary infection Abstrak—COVID-19 adalah penyakit yang muncul yang mempengaruhi kondisi tertentu.Namun, sebuah laporan baru-baru ini menunjukkan terjadinya hiperglikemia tanpa adanya diabetes pada pasien COVID-19. Penelitian ini bertujuan untuk meninjau secara sistematis bukti terbaru tentang hiperglikemia pada pasien COVID-19. Penelitian literatur dilakukan dengan menggunakan empat mesin pencari, yaitu Google Scholar, PubMed, ScienceDirect, dan ProQuest, dan terbatas hanya pada manuskrip berbahasa Inggris dan diterbitkan dari Februari 2020 hingga September 2020. SARS-CoV-2 dapat merusak pankreas dengan menyebabkan kerusakan pada pankreas. struktur sel β yang menyebabkan gangguan metabolisme glukosa dan memperburuk diabetes yang sudah ada sebelumnya atau menentukan munculnya hiperglikemia pada kelompok non-diabetes. Peradangan juga memainkan peran penting utama dalam hiperglikemia terkait COVID-19. Hiperglikemia meningkatkan kerentanan paru-paru, dengan mendorong dan memfasilitasi masuknya SARS-CoV-2 ke dalam sel inang, dan menurunkan fungsi paru-paru. Selain itu, angka mortalitas dan morbiditas yang diperkirakan meningkat karena hiperglikemia. Adanya kadar glukosa yang tinggi dikaitkan dengan perkembangan keparahan COVID-19. Dengan demikian, kadar glukosa harus diperhatikan, baik pada pasien dengan diabetes saat ini atau tanpa adanya diabetes. Pemeriksaan dan pemantauan kadar glukosa mungkin menjadi alat yang berguna untuk mencegah derajat keparahan COVID-19. Kata kunci: diabetes mellitus, SARS-CoV-2, peningkatan kadar glukosa, infeksi paru